Influence of increased body mass and body composition on cycling anaerobic power - Maciejczyk, M.; Wiecek, M.; Szymura, J.; Szygula, Z.; Brown, L. E. (The Journal of Strength and Conditioning Research, 2015)
Recent evidence suggests that not only body fat (BF) but high lean body mass (HLBM) adversely affects aerobic performance and may reduce aerobic endurance performance as well. However, the influence of body composition on anaerobic performance remains controversial. This study aimed to examine the effects of increased body mass (BM) and body composition on cycling anaerobic power. Peak power (PP) and mean power (MP) measurements were conducted in 2 groups of men with similar total BM but different body compositions resulting from (a) high level of BF [HBF group] or (b) high level of lean body mass [HLBM group] and in a control group. Peak power and MP were calculated in absolute values, relative to BM and lean body mass (LBM), and using allometric scaling. Absolute PP and MP were significantly higher in the HLBM group compared with the control and HBF groups. However, PP and MP relative to BM and using allometric scaling were similar in the HLBM and control groups, yet significantly higher than in the HBF group. There were no significant differences between groups in PP and MP when presented relative to LBM. Therefore, it seems that it is not BM but rather body composition that affects PP. Increased BM, resulting from increased LBM, does not adversely affect cycling anaerobic power, but a BM increase resulting from an increase in BF may adversely affect PP. Therefore, coaches and athletes should avoid excess BF to maximize cycling anaerobic power.